Optimal Design of Power-On Downshift Control of Series-Parallel Hybrid Transmission Based on Motor Active Speed Regulation - Xiangyang Xu; Kun Guo; Xuewu Liu; Hongzhong Qi; Peng Dong; Shuhan Wang; Wei Guo (Energies, 2022)
Multi-speed transmission is the main development direction of hybrid transmission, which has brought higher shift quality requirements than traditional fuel vehicle transmission. However, there is less research on the shifting control of hybrid transmission, especially for the shifting control of dedicated hybrid transmission (DHT), which uses the wet clutch as a shift element. This paper studies the power-on downshift process of a two-speed series-parallel hybrid transmission, proposes a shifting control strategy based on motor active speed regulation, and deeply analyzes the causes of maximum impact during the shifting process. The results show that the reverse torque produced in the process of eliminating the remaining slip is the root cause of the maximum impact. On this basis, two optimization strategies are proposed to reduce the shift impact and improve the shift quality. The simulation results show that the proposed optimization strategies can effectively suppress the shift impact. In the meanwhile, for any control pressure of the OG (off-going) clutch in the speed phase within the range of (2.44–2.53 bar), a high shift quality in which the maximum impact is controlled lower than 10 m/s3 can be achieved, which has high engineering value and practical significance.